Comparison between Portable Pulse Oximeter and Conventional ICU Pulse Oximeter measurements in healthy adults: A Cross Sectional Study - Adil Khan; Bushra Rabbani; Aashir Jameel; Beena Khan; Tahir Husain; Jameel Ahmed (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
ABSTRACT: Objective: To assess the agreement between oxygen saturation reading between portable pulse oximeter and conventional ICU monitor pulse oximeter. Methods: This cross-sectional study was conducted at Department of Medicine, Fatima Hospital Baqai Medical University, Karachi, from 1st March 2023 to 31st March 2023. Participants in the study in- cluded healthy health care workers and medical students who were over the age of 18 and did not have any known co-morbid conditions like hypertension or diabetes that may affect peripheral perfu- sion. None of the participants had hypotension, clinical evidence of anemia, fingernail paint or poor peripheral perfusion as these are the factors that may influence pulse oximetry readings. Both the portable pulse oximeter and the traditional intensive care unit (ICU) monitors were utilized to take and record the oxygen saturation levels of each of the ten fingers in a sequential manner while the patient was seated. Data was analyzed using SPSS version 22. Readings of both instruments were com- pared employing Regression analysis. Bland-Altman analysis was applied to measure the level of agreement between readings of portable pulse oximeter and conventional ICU monitors. Results: Total 200 participants were enrolled for this study and most of them were from younger age group. (Mean age of participants = 33.05 ± 10.31). There was no significant difference between oxy- gen saturation readings of respective finger from portable pulse oximeter and conventional ICU moni- tors on regression analysis (p > 0.05). Highest mean oxygen saturation was recorded in right middle finger using portable pulse oximeter (98.71 ± 1.21). On the ICU monitor pulse oximeter, it was 2nd highest in right middle finger (98.33 ± 2.49). Therefore, Bold-Altman analysis applied between oxygen saturation reading for two devices in right middle finger and was found to be comparable. (Mean dif- ference (bias) = 0.375 with 95% confidence interval). Conclusion: Modern portable pulse oximeters can reliably be used to rule out hypoxemia.